2018
DOI: 10.11607/jomi.6257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taper Angle and Sealant Agents on Bacterial Leakage Along the Implant-Abutment Interface: An In Vitro Study Under Loaded Conditions

Abstract: Differences in taper angles in the internal conical connections had no significant effect on leaked bacterial counts or the frequency of bacterial contamination under dynamic loading. The application of 2% chlorhexidine gel or a silicone sealant can reduce the leaked bacterial counts and reduce the frequency of bacterial leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…The results of studies that used bacteria to measure microleakage are more consistent with reality compared to the use of methylene blue. (6,11) In the present study, the size of microgap was 0.99±0.39 µm in the GapSeal group and 3.04±0.54 µm in the control group. Bacteria ranged in size from 0.2 to 5 µm.…”
Section: Resutlsupporting
confidence: 47%
See 4 more Smart Citations
“…The results of studies that used bacteria to measure microleakage are more consistent with reality compared to the use of methylene blue. (6,11) In the present study, the size of microgap was 0.99±0.39 µm in the GapSeal group and 3.04±0.54 µm in the control group. Bacteria ranged in size from 0.2 to 5 µm.…”
Section: Resutlsupporting
confidence: 47%
“…The shape of the abutment-implant junction and dynamic loading can increase micromovement and create a pumping effect, affecting leakage of bacteria and liquids. (7,11,19) in some previous studies, the amount of leakage has been studied statically. In 2011, Lorenzoni et al showed that microleakage and gap at the implant-abutment interface were present in two types of hexagonal implants; however, the samples were not cyclically loaded.…”
Section: Resutlmentioning
confidence: 99%
See 3 more Smart Citations